Nine-year changes in self-reported problems with vision and hearing among older adults: do subjective age views matter? - Wettstein, Markus; Wahl, Hans-Werner; Spuling, Svenja M. (Aging & mental health, 2021)
So far, little is known about linkages between subjective age views and long-term changes in vision and hearing. We examined the predictive role of two key measures of subjective age views (attitude toward own aging [ATOA]; aging-related cognitions comprising continuous growth, social loss, and physical decline) for changes in self-reported problems with vision and hearing over a period of up to 9 years. A subsample of the German Ageing Survey was used, consisting of 2,499 older adults. Controlling for socio-demographic characteristics, self-rated health, and depressive symptoms, we found that with increasing age, more favorable ATOA scores, as well as higher scores on continuous growth and lower scores on physical decline, were associated with fewer self-reported vision problems at baseline. With advancing age, more favorable ATOA scores were also related with fewer hearing problems at baseline. However, among individuals with an older baseline age, more favorable ATOA scores were associated with a steeper increase in vision problems. Higher scores on continuous growth were related with less increase in hearing problems, independent of age. Our findings suggest that subjective age views predict individuals’ self-reported vision and hearing problems.
Online publiziert: 28. September 2020
Gesehen am 26.08.2025